FEATURES OF THE 24-HOUR BLOOD PRESSURE PROFILE IN PATIENTS WITH ARTERIAL HYPERTENSION AND VARIOUS CARDIAC RHYTHM DISORDERS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The aim of the study is to analyze the characteristics of the 24-hour blood pressure (BP) profile in patients with arterial hypertension (AH) complicated by various cardiac rhythm disorders. The interrelationships between the type of arrhythmia and the parameters of 24-hour blood pressure monitoring (ABPM) are examined.